A GENERALIZED CODE FOR COMPUTING CYCLIC REDUNDANCY CHECK - Ghosh, Debopam; Mitra, Arijit; Mukhopadhyay, Arijit; Dawn, Aniket; Ghosh, Devopam (International Journal of Students' Research in Technology & Management, 2015)
This paper focuses on developing a generalized CRC code where the user can vary the size of the generator polynomial [1] such as 9 bits (CRC-8), 17 bits (CRC-16), 33 bits (CRC-32), 65 bits (CRC-64). The working of the code has been shown taking an example and the resulting simulations obtained are shown.